COMPUTER MODELING OF STURGEON POPULATION OF THE CASPIAN SEA WITH TWO TYPES OF APERIODIC OSCILLATIONS - Perevaryukha, A. Yu. (Radio Electronics, Computer Science, Control, 2014)
The article suggests the original computer model of the life cycle of sturgeon populations of the Caspian Sea, currently included in the «Red Book» since 2010. In our model was implemented event-stage computing structure that includes continuous and discrete components of the time. Features of the dynamics of the new model considered by us on the basis of the numerical solution of a finite sequence of the Cauchy problem for the system of equations describing the subsided of number of individuals in generations. As a result, we obtained the functional dependence, which be of interest to ichthyologists and which has two local extrema. The possibility of attraction of the trajectory to the two attractors and the appearance an aperiodic transition regime is established. After the bifurcation of the disappearance of two nontrivial stationary points arises an interval attractor. For this type of attractor on the Guckenheimer classification is observed the phenomenon of boundary crisis that for the sturgeon populations is interpreted as an event that threat to their continued existence.